101 ways to make training active - Silberman, Melvin L.; Lawson, Karen (Johannesburg : San Diego : Pfeiffer, 1995)
When it was first published in 1995, Mel Silberman's 101 Ways to Make Training Active became an instant bestseller. Now this revised and updated second edition offers the same dynamic approach and several completely new case examples. The examples support each exercise and highlight real-time uses of the highly successful Active Training method. In addition, the book includes 200 training tips that form the nuts-and-bolts of successful active training. These tips incorporated in the book's top ten lists show how to build quality, activity, variety, and direction into your training programs. For the first time 101 Ways to Make Training Active features a CD-ROM containing all the original "Top Ten Trainers Tips and Techniques" lists for easy reproduction and distribution.
Keywords: Active learning; Teaching; Adult learning